O monitoramento eletrônico de presos nas prisões cautelares - Santos, Marcio Cursino dos (2013)
The following dissertation has as an scope the coping of the State s right of monitoring the arrested that have on their disfavor the decree of any of the precautionary arrestments, considering that in our times the utilization of the current criminal sentence monitoring condemnatory with transit in the judged already is part of the toil of the Execution Criminal Law, with the right of the intimacy of the arrested that from the monitoring and intensification of the State under the individual becomes more intense, therefore the State instead of providing a pseudo freedom, actually intensify the surveillance of that citizen preventively arrested aims on this research show that the electronic monitoring mitigates some constitutional values in the Democratic State of Law